Elemental growth of oxide thin films - Wu, C (2010)
This thesis reports on the elemental growth of oxide thin films including TiOx, BaOx and BaxTiyOz by Ti/Ba deposition and oxidation. The films were grown on two different substrates, Au(111) and SrTiO₃(001), and studied using a variety of surface characterisation techniques. On the reconstructed Au(111) surface, three different TiOx structures were obtained with increasing Ti amounts deposited: a (2 × 2) Ti₂O₃ honeycomb structure, a pinwheel structure that is the result of a Moiré pattern, and a triangular island TiO1.30 structure. The structures arise from raised Ti coverages and have increased Ti densities. Although Ba deposited on the reconstructed Au(111) has a weak interaction with the substrate, the BaOx thin films can grow epitaxially and lift the Au(111) reconstruction. Two well-ordered phases, a (6 × 6) and a (2√3 × 2√3) BaOx structure, were obtained which may have octopolar-based surface structures. For Ba & Ti deposition on Au(111), a locally ordered (5 × 5) BaxTiyOz structure was observed in the sub-monolayer regime. What is more interesting is the possible formation of a BaO-TiO surface alloy with short-range ordering achieved by Ba deposition on the (2 × 2) Ti₂O₃-templated Au(111) surface. This is the first time that surface-alloying has been observed for oxides. When Ti is deposited onto the SrTiO₃(001) surface, it is incorporated into the substrate by forming a variety of Ti-rich SrTiO₃ surface reconstructions, such as c(4 × 2), (6 × 2), (9 × 2) and (√5 ×√5)-R26.6°. Ti deposition provides a completely different route to obtaining these reconstructions at much lower anneal temperatures than the previously reported preparation procedures involving sputtering and annealing the SrTiO₃ sample. Anatase islands with (1 × 3) and (1 × 5) periodicities were also formed by increasing the Ti deposition amount and post-annealing. Reconstructed SrTiO₃ substrate surface has a lattice that differs from the bulk crystal and affects the epitaxial growth of BaO, however, a locally ordered BaOx structure was observed on the sputtered substrate with a growth temperature of 300 °C. Depositing Ba & Ti on SrTiO₃(001) results in the formation of BaOx clusters and the Ti incorporation into the substrate, forming the familiar Ti-rich SrTiO₃ surface reconstructions.